Non-high-density lipoprotein cholesterol may predict the cardio-cerebrovascular risk in patients on maintenance hemodialysis - Denggui Luo (BMC, 2021)
Abstract Background Non-high-density lipoprotein cholesterol (non-HDL-C) may be an independent risk factor for cardio-cerebrovascular disease (CVD); however, the cutoff level in patients on maintenance hemodialysis (MHD) is unknown. Methods This was a retrospective multicenter study of MHD patients treated at 10 dialysis centers in Guangdong Province from July 1, 2016, to April 1, 2017. Laboratory test data were collected and CVD complications and outcomes recorded. Results In total, 1288 eligible patients were included in this study; the non-HDL-C interquartile range was 2.76 (2.24–3.45) mmol/L. Over a median follow-up time of 24 months, 141 patients developed CVD. The non-HDL-C level was a principal risk factor for such events (P < 0.05; 95% confidence interval 0.800–0.842). The maximum Youden index was 0.549 and the best cutoff > 3.39 mmol/L. Conclusion Higher baseline non-HDL-C levels may increase the CVD risk in MHD patients. Thus, non-HDL-C effectively predicts CVD.